THE EFFECT OF EXPERIENTAL MARKETING, SERVICE QUALITY AND PROMOTION ON CUSTOMER LOYALTY AT ROLAND BAKERY AND CAFE JEMBER - Bella Aurellia Natalie; J. E. Sutanto; Moses Soediro; Adrie Oktavio (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Research entitled "The influence of experimental marketing, service quality and promotion on customer loyalty at Roland Bakery and Café Jember" has four objectives, namely: (1) Knowing the effect of experimental marketing on customer loyalty, (2) Knowing the effect of service quality on customer loyalty, (3) Knowing the effect of promotion on customer loyalty, (4) Knowing the effect of experimental marketing, service quality and promotion simultaneously on customer loyalty. Roland Bakery and Café is a Food and Beverage business located in Jember Regency which was established in 2000 selling various appetizer to dessert menus. This study uses descriptive quantitative research methods. The population in this study are Roland Bakery and Café customers who make purchases at least 3 times a month. This research sample amounted to 160 people, data collection was carried out online and offline. Data processing is done by multiple linear analysis using the IBM SPSS 25 application as a tool. The results of this study are: (1) Experiental marketing significantly affects customer loyalty (2) Service quality significantly influences customer loyalty (3) Promotion significantly influences customer loyalty (4) Experiental marketing, service quality and promotion are simultaneous against customer loyalty.